Fiscal Decentralization and Ethnic Politics in Macedonia - Aleksandra Maksimovska; Aleksandar Stojkov; Patrick Schmidt (Lex localis - Journal of Local Self-Government, 2015)
Competing ethno-centered strategies over the local fiscal resources can seriously undermine political and economic stability of ethnically diverse societies. This study investigates the causal link between ethnic diversity and local government finances by focusing on the case of Macedonia. In particular: whether fiscal decentralization is used as a part of broader strategy for prevention and mitigation of inter-ethnic conflicts. The main argument is that low level of political culture and inter-ethnic tensions are frustrating the development of the government policy along a course of decentralization. The study confronts two emerging scenarios regarding decentralization and inter-ethnic relations. The first scenario puts the economic development at the forefront for country’s stability and treats decentralisation as a driving force to achieve this goal. Ethnic problems are expected to be solved along this path as rising economic stability reduces the inter-ethnic tensions. In the second scenario, the inter-ethnic stability is the main pillar of the country’s stability, which is expected to be accomplished through decentralisation. The paper analyses and synthesizes pros and cons of two scenarios from administrative, legal, political and economic perspectives.